Caffeine degradation in leaves and fruits of Coffea arabica and Coffea dewevrei - Pierre Vitória, Angela; Mazzafera, Paulo (Pesquisa Agropecuaria Brasileira, 1998)
The coffee species Coffea dewevrei and Coffea arabica have marked differences in caffeine metabolism and the control of the caffeine content during fruit ripening and leaf aging is still not clear. The aim of this work was a detailed investigation on the alkaloid degradation in young and aged leaves, and immature and mature fruits of these species. Young and aged leaves, and immature and mature fruits were fed with [2-14C] caffeine. After an incubation period they were extracted for [2-14C] caffeine and metabolites and analysed by reversed-phase liquid chromatography and radiocounting of collected fractions. In leaves and fruits of Coffea dewevrei there were higher degradation rates of caffeine. In both species, compared to young tissues, aged leaves and mature fruits presented lower capacity to degrade the alkaloid, what was shown by the low radioactivities detected in the metabolites formed in the degradation pathway. Radioactivity was detected in 7-methylxanthine, which is also a precursor in the caffeine biosynthesis. The data support the conclusion that the ratio between biosynthesis and biodegradation controls the variation of the caffeine content during fruit ripening and leaf aging in C. arabica and C. dewevrei.